Peers as Change Agents 2021
DOI: 10.1093/med-psych/9780190068714.003.0003
|View full text |Cite
|
Sign up to set email alerts
|

Peers as Culturally Relevant Change Agents

Abstract: As the United States’ school-age population has become increasingly diverse, it is critical that the curricula, instruction, assessments, and interventions in schools are culturally relevant, reflecting the values and lived experiences of children and families. In this chapter, we posit that peer-mediated interventions are viable strategies that can be used to improve the cultural relevance of interventions in schools. After reviewing culturally relevant school-based service delivery, we offer four reasons sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…RJ practices can fit seamlessly into culturally relevant MTSS models, and common practices include restorative circles (i.e., meetings to repair harm and discuss group dynamics), restorative chats (i.e., adult-guided amend-making meetings), and classroom agreements (i.e., a process for creating classroom rules and culture describing how students and staff will interact with one another; Nese et al, 2021). These strategies are included in the various peer-mediated interventions that have strong theoretical foundations for success with Black students (Collins et al, 2021). Gregory et al (2016) found that teachers exhibiting strong implementation of RJ strategies had better relationships with their minoritized students and issued fewer office discipline referrals to Black and Latinx students than teachers who implemented RJ less effectively.…”
Section: Recommendations For Practicementioning
confidence: 99%
“…RJ practices can fit seamlessly into culturally relevant MTSS models, and common practices include restorative circles (i.e., meetings to repair harm and discuss group dynamics), restorative chats (i.e., adult-guided amend-making meetings), and classroom agreements (i.e., a process for creating classroom rules and culture describing how students and staff will interact with one another; Nese et al, 2021). These strategies are included in the various peer-mediated interventions that have strong theoretical foundations for success with Black students (Collins et al, 2021). Gregory et al (2016) found that teachers exhibiting strong implementation of RJ strategies had better relationships with their minoritized students and issued fewer office discipline referrals to Black and Latinx students than teachers who implemented RJ less effectively.…”
Section: Recommendations For Practicementioning
confidence: 99%